Gastric ischemic preconditioning may reduce the incidence and severity of anastomotic leakage after οesophagectomy: a systematic review and meta-analysis. Issue 10 (6th May 2020) - Michalinos, Adamantios; Antoniou, Stavros A; Ntourakis, Dimitrios; Schizas, Dimitrios; Ekmektzoglou, Konstantinos; Angouridis, Aris; Johnson, Elizabeth O
Summary: Anastomotic leakage after esophagectomy is a severe and life-threatening complication. Gastric ischemic preconditioning is a strategy for the improvement of anastomotic healing. Aim of this systematic review and meta-analysis is to investigate the impact of gastric ischemic preconditioning on postoperative morbidity. A systematic literature search was performed to identify studies comparing patients undergoing gastric ischemic preconditioning before esophagectomy with nonpreconditioned patients. Meta-analysis was conducted for the overall incidence of anastomotic leakage, severe anastomotic leakage, anastomotic stricture, postoperative morbidity, and mortality. Mantel–Haenszel odds ratios (ORs) and 95% confidence intervals (CIs) were calculated. Subgroup analyses were performed concerning preconditioning technique, the interval between preconditioning and surgery and the extent of preconditioning. Fifteen cohort studies were identified. Gastric preconditioning was associated with reduced overall incidence of anastomotic leakage (OR 0.73; 95% CI, 0.53–1.0; P  = 0.050) and severe anastomotic leakage (OR 0.27; 95% CI, 0.14–0.50; P  < 0.010), but not with anastomotic stricture (OR 1.18; 95% CI 0.38 to 3.66; P  = 0.780), major postoperative morbidity (OR 1.03; 95% CI 0.45 to 2.36; P  = 0.940) or mortality (OR 0.69; 95% CI 0.39 to 1, 23; P  = 0.210). Subgroup analyses did not identify any differences between embolization and ligation while increasing the interval between preconditioning and esophagectomy as well as the extent of preconditioning might be beneficial. Gastric ischemic preconditioning may be associated with a reduced incidence of overall and severe anastomotic leakage. Randomized studies are necessary to further evaluate its impact on leakage, refine the technique and define patient populations that will benefit the most.